Immunogenetics in stem cell donor registry work: The DKMS example (Part 2). (7th February 2020) - Schmidt, Alexander H.; Sauter, Jürgen; Baier, Daniel M.; Daiss, Jessica; Keller, Andreas; Klussmeier, Anja; Mengling, Thilo; Rall, Gabi; Riethmüller, Tobias; Schöfl, Gerhard; Solloch, Ute V.; Torosian, Tigran; et al.
Abstract: DKMS is a leading stem cell donor registry with more than 9 million donors. Donor registry activities share many touch points with topics from immunogenetics or population genetics. In this two‐part review article, we deal with these aspects of donor registry work by using the example of DKMS. In the second part of the review, we focus on donor typing of non‐HLA genes, the impact of donor age, gender and CMV serostatus on donation probabilities, the identification of novel HLA, KIR and MIC alleles by high‐throughput donor typing, the activities of the Collaborative Biobank and pharmacogenetics in the donor registry context.